Determination of Interlayer Stresses for Multilayered Materials by using Biquadratic Basic Functions - Muradoglu, Zahir; Urbanovich, Tatsiana; Yazici, Vildan (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we deal with the boundary value problem for the Lame system, modeling the contact problem for a multilayered material. We use biquadratic basic functions to obtain the transmission conditions on the boundaries of interlayer by the Finite Element Method. We analyze the interlayer stresses.